Struktur Komunitas Makrozoobenthos Sebagai Indikator Kualitas Perairan di Pantai Serangan Provinsi Bali - Yulihatul Meisaroh; I Wayan Restu; Dewa Ayu Angga Pebriani (Journal of Marine and Aquatic Sciences, 2019)
Serangan Island is a small island located approximately 5 km in south of Denpasar City and has a maximum length of 2.9 km and a width of 1 km which is administratively as part of the Denpasar City, Bali Province. Serangan Island is widely used for aquaculture and fisheries activities, moreover Serangan is also used as tourism activities, transportation routes, the harbour of ships and residences which may have impact on the aquatic ecosystem balance. The purpose of this research is to know how the structure of macrozoobenthos community and the water quality condition in Serangan Island. The research was conducted on February to March 2017 by using descriptive quantitative method in 3 research stasions. The result showed that there are 23 species of macrozoobenthos that consists of 7 classes, namely Gastropods, Bivalve, Crustacea, Echinoidea, Asteroidea, Ophiuroidea, and Holothuroidea. The highest total of abundance was at station 1 about 46,8 ind/m2. The diversity index ranged from 0,66-2,14 and the equibility index ranged from 0,60-0,81, while the dominance index ranged from 0,17-0,63. Based on the criteria of the Shanon-Wiener diversity index (H'), the diversity index at station 1 and 2 indicates moderate diversity which has moderate species distribution and moderately polluted waters, whereas the value of the diversity index at station 3 indicates that the diversity in this stasion is low, showed by low abundance of species, low stability of the community and severe polluted condition.